Thermal decomposition behaviour and numerical fitting for the pyrolysis kinetics of 3D spongin-based scaffolds. The classic approach. (May 2021) - Żółtowska, Sonia; Koltsov, Iwona; Alejski, Krzysztof; Ehrlich, Hermann; Ciałkowski, Michał; Jesionowski, Teofil
Abstract: The kinetic parameters of thermal degradation of 3D skeletal biopolymer spongin - isolated from the marine demosponge Hippospongia communis, using thermogravimetric analysis (TG) were evaluated. The kinetic parameters of the pyrolysis in a nitrogen atmosphere were calculated using standard methods, including a model-fitting approach (Coats–Redfern method) and the model-free iso-conversional Friedman, Kissinger–Akahira–Sunose (KAS) and Ozawa–Flynn–Wall (OFW) methods. Based on the kinetic parameters obtained from the respective equations, the changes of entropy ( ΔS), enthalpy ( ΔH), and free Gibbs energy ( ΔG) were evaluated using the theory of the active complex of the reagent. It was found that the chemical reaction model best describes the experimental data. The activation energies calculated by the Coats–Redfern method were in the range 39.3–48.7 kJ/mol. The calculated values of kinetics parameters are slightly lower than for the commercial polyurethane foams. Nevertheless, this study provides a comprehensive insight into the pathway, mechanism, and outcomes of pyrolysis of spongin-based scaffolds with the relation to the physicochemical characteristics of finally obtained carbon materials. Moreover, a critical discussion of the obtained results is given, with regard to the physical meaning of the applied approximations. Graphical abstract: Image 1 Highlights: Kinetics of spongin-based scaffold pyrolysis were studied using different approaches. The reaction profile of spongin biomaterial pyrolysis was determined. The Coats–Redfern, KAS, OFW, and Friedman methods were investigated. Values of parameters EA and A differ depending on the approach used. EA values calculated by the Coats–Redfern method were in the range 39.3–48.7 kJ/mol.